TINGKAT KEPERCAYAAN PELANGGAN TERHADAP INTERNET STORE DAN KESEDIAAN UNTUK MEMBELI - Meyliana, Meyliana (Proceedings of KNASTIK, 2012)
The rapid growth in the marketplace is highly influenced by the greatest developmentand use of the internet that can answering the needs of to up-to-date information aboutproducts and any other things while can be accessed everywhere and anywhere. This iscalled e-Marketing or marketing-based electronic. E-marketing become very importantfor the companies that sell its product online or its often called internet store. The studywas conducted to observe the correlation between level of customer trust on theInternet store and the willingness to buy the products through the internet store. Thestudied site is www.bhinneka.com. The research method using six variables: PerceivedSize, Perceived Reputation, Trust in Store, Attitude, Risk Perception and Willingness toBuy. The hypothesis was tested using correlation analysis and regression analysis. Thestudy concluded that level of customer trust on the internet stores have relationship andimpact on their willingness to buy through the internet store.